METODE PEMBELAJARAN KARYA WISATA (STUDI TOUR) DALAM TELAAH TAFSIR AL-QUR’AN SURAH AL-ANKABUT AYAT 20 DAN HADIST - Mirna, Mirna Kartika; Kristina Imron; Alimron (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2023)
Learning is the process of interaction between students and educators and learning resources in a learning environment. Before carrying out the learning process, a teacher determines or chooses the approach and method to be used so that the learning objectives that have been prepared can be achieved. In this study, the author will discuss the method of learning tourist works (Study Tour) in the study of the interpretation of the Qur'an, surah al-Ankabut verse 20 and Hadith. To achieve an expected target in the world of education, an appropriate method is needed. In accordance with what is stated in Al-Ankabut verse 20 where the content of the verse about educational methods is very interesting to be explored further and deepened. Surah Al-Ankabut verse 20 in the learning method has important urgency and relevance. In Islam, trips and tours done with good intentions and right purpose can be considered as worship. In addition, through travel and sightseeing, one can also admire the beauty of God's creation and contemplate His greatness. By using library research methods